2022
DOI: 10.1177/00315125221093898
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Mental Fatigue and Emotional Suppression on the Performance of High-Intensity Endurance Exercise

Abstract: This study investigated the extent to which mental fatigue and emotional suppression affected exercise endurance. Twelve participants performed cycling endurance tests at 80% of their peak power up to the point of exhaustion. Two experimental conditions (mental fatigue [MF] and emotion suppression conditions [ES]) and a control condition (CO) were administered. Participants responded to psychological measures throughout the exercise trials. Both MF and ES conditions hindered exercise performance relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…A total of 50 effect sizes were selected for eligibility, but 4 were discarded because descriptive data were not reported and authors did not provide raw data upon request. 3 A total of 46 effect sizes from independent samples were included in the meta-analysis [ 23 , 24 , 61 98 ]. A disclosure table containing the list of 50 effects selected for eligibility, including those included in meta-analysis and the literature search output, can be found at https://osf.io/5zbyu/ .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 50 effect sizes were selected for eligibility, but 4 were discarded because descriptive data were not reported and authors did not provide raw data upon request. 3 A total of 46 effect sizes from independent samples were included in the meta-analysis [ 23 , 24 , 61 98 ]. A disclosure table containing the list of 50 effects selected for eligibility, including those included in meta-analysis and the literature search output, can be found at https://osf.io/5zbyu/ .…”
Section: Resultsmentioning
confidence: 99%
“…may condition, in general, these decreases in mood and the results of the test. In this sense, in the study by Schlichta et al [ 41 ], in which participants (young adults) were subjected to intense physical exercise (at 80% of their maximum power) until exhaustion under two different conditions (mental fatigue and suppression of emotions), they observed that, in relation to the control group, those who were subjected to some conditions during the test had difficulty with their exercise performance, there being, on the contrary, no statistically significant differences between the two conditions. In the same line, in the study of Van Cutsem [ 42 ], he pointed out that the duration and intensity of a physical task seem to be important factors in the decrease of physical performance due to mental fatigue, the latter being subscribed to a greater perceived effort.…”
Section: Discussionmentioning
confidence: 97%
“…A visual analog scale (VAS) with 10 cm lines was employed to assess exercise-induced fatigue in this study. This method is relatively efficient in evaluating acute fatigue ( Schlichta et al, 2022 ). The questionnaire comprised five questions related to physical fatigue, cognitive fatigue, sleepiness, decreased thinking clarity, and attention, all of which were completed on a paper-based form.…”
Section: Methodsmentioning
confidence: 99%